Descartes-Snell law of refraction with absorption - Kovalenko, S.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
The state of the art in the theory of optical constants of matter is considered for different spectral ranges of light absorption. It is stressed that up to now no there exists no commonly accepted formula for calculation of refractive index in the X-ray region. Starting from three different approaches, an analysis is made of relations between the angles of refraction and incidence in the case of a transparent medium-absorbing medium interface. Through analysis of the corresponding plots each of relations is estimated from the standpoint of possibility for its practical application. A novel version of the Descartes-Snell law is advanced. For the first time an expression (15) is obtained that is completely substantiated, both mathematically and physically. It may be recommended for use, first of all, when calculating multiplayer coatings in the X-ray optics units. It is stated that further investigations in this area are required, especially when performing experiments for different regions of optical and X-ray spectra.